TOXOPLASMOSIS AS AN OPPORTUNISTIC PROTOZOAN INFESTATION AND ITS SIGNIFICANCE IN TRANSPLANTATION - D. B. Goncharov; N. I. Gabrielyan; E. V. Abbazova; E. S. Ievleva; T. V. Krupenio (Вестник трансплантологии и искусственных органов, 2016)
The pathogen of toxoplasmosis called Toxoplasma gondii is able to persist for a long time in various human tissues. Toxoplasmosis is referred to as an opportunistic disease, since it presents a danger to the life of the patient for the immune dysfunction. Reactivation of latent infestation in HIV infection and transplantation procedures is a serious problem for healthcare. If a dominant clinical form in patients with HIV infection is represented by cerebral toxoplasmosis, then a broader range of lesions is observed after organ transplantation. Toxoplasmosis myocarditis and pericarditis are reliably more frequently observed. This paper analyzes mortality rate in transplantation of various organs, timing of invasive reactivation in the postoperative period and relation between reactivation and withdrawal of preventive drugs. Objectively it is rather difficult to diagnose the disease due to inaccessibility of the pathogen, atypical clinical picture and low sensitivity of laboratory indication methods. In this regard, there is a useful experience of foreign and domestic research studies in searching and using clinical, instrumental, immunological and molecular criteria of reactivation of toxoplasmosis in human immunodeficiency. The given facts convincingly demonstrated the danger of toxoplasmosis; the role of the disease is shown for various fields of medicine, particularly in transplantation of organs and tissues.